Entrevaguear e pesquisar em educação: livros de artistas-professores [e o que se cria] no deambular entre o estágio curricular supervisionado e o Programa Residência Pedagógica - Durante, Rafael Agatti (2020)
This research aims to present the creation processes of Books by Artist-Teachers (BATs) with students of the Supervised Academic Internship 4 course, in the Visual Arts Education Major of the Federal University of Santa Maria (UFSM) in 2019. These students are also participants of the Visual Arts Subproject in the Pedagogical Residency Program of the above-mentioned institution. The theoretical scope used embraces the philosophies of difference and finds encouragement in the company of Deleuze (2016), Deligny (2018) and Silveira (2001), some of the most present authors in this research. This dissertation enables the following thought as a problematic: how a wandering through BATs moves creation processes between the Pedagogical Residency Program and the Supervised Academic Internship? As a methodological movement, it bets on the strength of roaming, that accepts and takes the research in its possibility of wandering through the territories of education and art, while it also enters into an experimental writing that happens in the middle of the creation process followed by silence and rain sounds, being on the watch of what affects this journey. Therefore, this research brings as materialities, the collection of images by places and the production of the BATs developed by the students, as well as poetry excerpts and (dis)encounters that enhanced the roaming. The results consist in the presentation of BATs as a notion initially thought by the author and performed in the collective with the students, as well as the manifestations of traces of going through erratic paths that took place as events went on, showing movements and what was possible to plot with the notion announced in education and art.